Purchase Decision at Hendyh's Brownies Bakery Based on Brand Image and Store Atmosphere - arief Hadian (Universitas Indo Global Mandiri, 2022)
The development of an increasingly modern era has an impact on business competition in Indonesia, especially in the culinary field. This makes entrepreneurs must continue to understand the needs, wants and demands of the market. In the midst of the era of rapid modernization, Hendhy's Brownies Bakery actually experienced a decrease in turnover every month. This research was conducted as a basis to determine the effect of Brand Image and Store Atmosphere on purchasing decisions at Hendhy's Brownies Bakery. The population in this study are customers who have purchased products at Hendhy's Brownies Bakery. The sample in this study amounted to 98 respondents with data collection methods using questionnaires and observation. Multiple linear regression analysis technique was used to determine the effect of the independent variable on the dependent variable. The results of this study indicate that there is a positive and significant influence between brand image and store atmosphere on purchasing decisions at Hendhy's Brownies Bakery. To improve the brand image at Hendhy's Brownies Bakery by maintaining the company's image, product image and consumer image well. And also to improve the store atmosphere is to pay attention to the general exterior, store layout, and good interior display.